Modulating built-in electric field via variable oxygen affinity for robust hydrogen evolution reaction in neutral media - Zhai, Lingling (2022)
Work function strongly impacts the surficial charge distribution, especially for metal-support electrocatalysts when a built-in electric field (BEF) is constructed. Therefore, studying the correlation between work function and BEF is crucial for understanding the intrinsic reaction mechanism. Herein, we present a Pt@CoOx electrocatalyst with a large work function difference (ΔΦ) and strong BEF, which shows outstanding hydrogen evolution activity in a neutral medium with a 4.5-fold mass activity higher than 20 % Pt/C. Both experimental and theoretical results confirm the interfacial charge redistribution induced by the strong BEF, thus subtly optimizing hydrogen and hydroxide adsorption energy. This work not only provides fresh insights into the neutral hydrogen evolution mechanism but also proposes new design principles toward efficient electrocatalysts for hydrogen production in a neutral medium.